Kawasaki Disease : Current Understanding of the Mechanism and Evidence-Based Treatment - Saji, Ben Tsutomu; Newburger, Jane W.; Burns, Jane C.; Takahashi, Masato (Springer Japan : Imprint: Springer, 2017)
This book provides the most up-to-date information on the clinical research into and medical management of Kawasaki Disease, and opens the door for new pathological insights. Its nearly 50 sections cover basic research, genetic backgrounds, bacterial and　biological　evidence, and medical　treatment　with　intravenous　immunoglobulin, steroids, and recent anti-cytokine approaches. It offers an invaluable resource for general pediatricians, pediatric and adult cardiologists, pediatric cardiac surgeons, infectious disease specialists, pediatric rheumatologists, epidemiologists, and basic researchers in these disciplines.
Keywords: Medicine.; Immunology.; Cardiology.; Pediatrics.; elektronické knihy; electronic books